A multidimensional approach in examining the role of self-efficacy on innovative work behavior: Evidence from the creative industry - Zulkifli Musannip Efendi Siregar; Yudi Nur Supriadi; Agus Setyo Pranowo; Ende; Nova Jayanti Harahap (Problems and Perspectives in Management, 2022)
Innovative work behavior is a significant factor for business success, including in the creative industry. This paper aims to explore the effect of self-efficacy on the innovative work behavior of employees in the creative industry sector. This study uses a quantitative research approach. It was conducted on small and medium enterprises in the creative industry sector in Labuhanbatu and South Labuhanbatu regencies, Indonesia. The participants in this study were employees and managers in the creative industry. The sampling technique is non-probability sampling. A total of 250 questionnaires were distributed, and 216 questionnaires were returned. Therefore, the samples in this study were 216 respondents. After the data were collected, they were processed by the Structural Equation Modeling (SEM) method, which uses a multidimensional approach to testing the hypothesis. The results revealed that innovative work behavior was influenced by self-efficacy. Based on the results of the multidimensional analysis, it was shown that the most influential dimension in measuring innovative work behavior was the idea champion. In addition, the strength dimension dominantly influenced self-efficacy as the most influential dimension. The originality/value of this paper is that the analysis using multidimensional analysis shows that self-efficacy can predict innovative work behavior. The SMEs in the creative industry are suggested to give support to enhance their capability to improve employee self-efficacy and innovative work behavior.